Hospital admission and risk assessment associated to exposure of fungal bioaerosols at a municipal landfill using statistical models (2018)
The object of this research to determine the statistical relationship and degree of association between variables: hospital admission days and diagnostic (disease) potentially associated to fungal bioaerosols exposure. Admissions included acute respiratory infections, atopic dermatitis, pharyngitis and otitis. Statistical analysis was done using Statgraphics Centurion XVI software. In addition, was estimated the occupational exposure to fungal aerosols in stages of a landfill using BIOGAVAL method and represented by Golden Surfer XVI program. Biological risk assessment with sentinel microorganism A. fumigatus and Penicillium sp, indicated that occupational exposure to fungal aerosols is Biological action level. Preventive measures should be taken to reduce the risk of acquiring acute respiratory infections, dermatitis or other skin infections.